2017
DOI: 10.21103/article7(3)_oa6
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Expressive Suppression and Cognitive Reappraisal Between Heart Disease and Generalal Population

Abstract: Aim: Heart disease and emotional disorders often co-occur, but effective role in dysregulation of heart disease that is often overlooked. Evidence suggests that people with heart disease are more problems in regulating their emotions.The study compared the re-evaluation of cognitive emotion regulation commonly used two strategies-and suppressionbetween heart disease and the general population.Methods: Sixty men (30 with heart complaints and 30 without the condition) were selected by convenience sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…In addition, cognitive reappraisal was related to lower distress in this study, and cognitive reappraisal has been related to health and well‐being in previous works (i.e., Mirlohi et al, 2017). Because emotional expression and cognitive reappraisal have been found to be adaptive coping strategies during confinement, psychological prevention and intervention programmes should address the identification, expression, and use of cognitive reappraisal strategies to manage emotions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, cognitive reappraisal was related to lower distress in this study, and cognitive reappraisal has been related to health and well‐being in previous works (i.e., Mirlohi et al, 2017). Because emotional expression and cognitive reappraisal have been found to be adaptive coping strategies during confinement, psychological prevention and intervention programmes should address the identification, expression, and use of cognitive reappraisal strategies to manage emotions.…”
Section: Discussionsupporting
confidence: 74%
“…In fact, attempts to suppress negative emotions have been linked to increased negative emotions (Dalgleish et al, 2009). In addition, cognitive reappraisal has been related to health and well‐being (Mirlohi, Mohajerin, Mirlohi, & Aref, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in cardiac patients and the general population, Mirlohi and colleagues (2017) studied emotion control strategies (reappraisal and suppression). Results showed that heart disease patients prefer suppression, and reappraisal was commonly used by the control group to modify their emotions (Mirlohi, Mohajerin, Mirlohi, & Aref, 2017).…”
Section: Discussionmentioning
confidence: 99%